(untitled) (Research, Society and Development, 2021)
This study aimed to analyze the association of self-reported barriers to the practice of physical activity and stage of behavior change in employees of a Teaching Hospital in southern Brazil. Cross-sectional study, which investigated 485 workers at a Teaching Hospital in southern Brazil, 313 women and 172 men. The variables analyzed were: level of physical activity, body mass index, waist circumference, age, smoking, alcohol consumption, hours spent sleeping, stage of behavior change and barriers to physical activity. Descriptive statistics were used in median, minimum and maximum values ​​to characterize the population, in addition to using the Mann-Whitney U test for comparison between genders. The Chi-square test (p<0.05) with Fisher correction was used, when necessary. In males, the barriers: not liking physical activity (p=0.018), fear of injury (p=0.003) and lack of company (p=0.005) showed a significant difference between inactive and active behaviors. The barriers; lack of free time, fear of injury and laziness showed a significant difference between age groups, not showing progression over time. The low level of physical activity can be considered a factor associated with greater complaints of limitations in the practice of physical activity.